Inhibition of Th2 Differentiation Accelerates Chronic Wound Healing by Facilitating Lymphangiogenesis - Bracha L. Pollack; Jeremy S. Torrisi; Geoffrey E. Hespe; Gopika Ashokan; Jinyeon Shin; Babak J. Mehrara; Raghu P. Kataru (Biomedicines)
Background/Objectives: Chronic wounds pose a significant healthcare burden, and there remains no effective animal model for study. We aimed to develop a mouse model of chronic wounds that remain open for at least 4 weeks and to investigate the role of the lymphatic system in wound healing. Methods: Full-thickness excisional wounds were created on the dorsal surface of mouse tails to simulate chronic wounds. Lymphatic drainage was assessed using FITC–dextran lymphangiography. Histology and immunofluorescence were used to analyze immune cell infiltration. The effect of inhibiting Th2 differentiation via IL-4 and IL-13 neutralization on wound closure was also evaluated. Results: Our chronic wound model was successful, and wounds remained open for 4 weeks. Impaired lymphatic drainage was observed extending beyond the wound area. Increased CD4+ T-helper cell infiltration and Th2 cell accumulation were observed in the impaired lymphatic drainage zone. Inhibition of IL-4 and IL-13 accelerated wound healing. Conclusions: Impaired lymphatic drainage and Th2-mediated inflammation contribute to delayed healing, and gradients of lymphatic fluid flow are associated with spatial differences in lymphangiogenesis. Targeting Th2 cytokines may offer a novel therapeutic approach for chronic wounds.